2007
DOI: 10.1177/097206340700900104
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Performance of Public Hospitals in Tamil Nadu

Abstract: Data envelopment analysis (DEA) was used to investigate the efficiency of a set of district hospitals in the state of Tamil Nadu. These facilities naturally provide primary and secondary care, but are also expected to function as health centres, addressing mostly preventive medicine, hygiene and other public health issues. This study aimed to obtain insight on their technical efficiency in light of their particular role. We have considered all the 29 district hospitals in the state. Variables chosen to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
2
4
0
1
Order By: Relevance
“…The finding of 50% district hospitals operating with technical inefficiency is similar to a study conducted in Gujarat state of India (17), whereas, a study conducted in Tamilnadu state found that 72% of the district hospitals were operating as technically inefficient during the year 2004–2005 (18). Another study conducted in Tamilnadu (19) revealed that 34.5, 41.3, 62, 55.2, and 51.7% of district hospitals were operating as technically inefficient during the years 2002–2003, 03–04, 04–05, 05–06, and 06–07, respectively.…”
Section: Discussionsupporting
confidence: 76%
“…The finding of 50% district hospitals operating with technical inefficiency is similar to a study conducted in Gujarat state of India (17), whereas, a study conducted in Tamilnadu state found that 72% of the district hospitals were operating as technically inefficient during the year 2004–2005 (18). Another study conducted in Tamilnadu (19) revealed that 34.5, 41.3, 62, 55.2, and 51.7% of district hospitals were operating as technically inefficient during the years 2002–2003, 03–04, 04–05, 05–06, and 06–07, respectively.…”
Section: Discussionsupporting
confidence: 76%
“…These techniques showed that VRS/CRS distinction was the most significant determinant of the performance differences in the DEA models tested. In fact; VRS models have been suggested by previous studies on hospital efficiency (Dash et al [42]; Mark et al [43]; Ozcan et al [44]; Ketabi [45]; Gautam et al [46]; Prakash and Annapoorni [47] and our results show that VRS models would be better for EDs as well. On the other hand, to determine whether using only a single output (number of emergency patients) or two outputs (number of emergency patients and number of referrals) made a significant difference in the efficiency rankings of the hospitals, we employed a novel approach utilizing outlier detection with regression.…”
Section: Conclusion and Further Suggestionssupporting
confidence: 72%
“…Hence, there are numerous reports of empirical nature that are making roads in evaluating the factors for efficient healthcare organizations in the states of India. The studies by Dash et al (2007Dash et al ( , 2010 and Sengupta and Mondal (2009) are some of the attempts at the individual state level. It is vastly understood that a fair view of the characteristics that are responsible for the changes in the functioning at the substate level is required to modify the various approaches and better manage the sector of health.…”
Section: Review Of Literaturementioning
confidence: 99%